The Effect of Tempe Flour Substitution on the Chemical and Organoleptic Quality of Mud Cake Based on Wheat Flour - Lucielya Jevita Kenenbudi; Retnani Rahmiati; Fadjar Kurnia Hartati; Imania Ayu Wulandari (Green Publisher Indonesia, 2026)
This study addresses the need to enhance the nutritional quality of traditional Indonesian foods, particularly kue lumpur, which is widely consumed but generally low in protein due to its reliance on wheat flour. As a locally available and protein-rich ingredient, tempeh flour offers potential as a functional substitute to improve both nutritional value and food diversification. Therefore, this research aims to evaluate the effect of tempeh flour substitution on the chemical and organoleptic quality of wheat-based kue lumpur. The study employed an experimental method using a Completely Randomized Design (CRD) with a single factor, namely the level of tempeh flour substitution (0%, 25%, 50%, 75%, and 100%), with three replications. Chemical properties were analyzed using Analysis of Variance (ANOVA), while organoleptic data were assessed using the Kruskal-Wallis test. The effectiveness of each formulation was determined using the De Garmo index. The results indicate that tempeh flour substitution significantly increases protein and fat content while reducing carbohydrate levels. However, it shows no significant effect on moisture content, color, taste, and texture, but significantly affects aroma. The optimal formulation was identified at 75% substitution, achieving a balanced improvement in both nutritional and sensory qualities. In conclusion, tempeh flour is a viable alternative ingredient to enhance the nutritional value of traditional kue lumpur while maintaining acceptable consumer preferences.